MLH1, MSH2, MRE11, and XRCC1 in Oral Leukoplakia and Oral Squamous Cell Carcinoma - Donís, Sergio Piñeiro; González, Alba Pérez; Alves, Monica Ghislaine Oliveira; Do Carmo Carvalho, Bruna F.; Ferreira, Camila C.P.; Almeida, Janete Dias [UNESP]; Iruegas, Elena Padín; Petronacci, Cintia M. Chamorro; Peñaranda, José M. Suárez; Sayáns, Mario Pérez (Wolters Kluwer, 2021)
Background: DNA damage is accumulated in the cells over time as the result of both exogenous and endogenous factors. The objective of this study was to analyze the immunohistochemical expression of the repair proteins in oral leukoplakia (OL) and oral squamous cell carcinoma (OSCC). Materials and Methods: Paraffin blocks were selected from the archives of the Laboratory of Hospital Clinico Universitario de Santiago de Compostela, Spain. The sample was composed of 16 cases of OL without dysplasia, 14 cases of OL with dysplasia, and 15 cases of OSCC. The patients' clinical data were collected and immunohistochemical analysis was performed for MLH1, MSH2, MRE11, and XRCC1. The data were submitted to the χ2and the Kruskal-Wallis (P≤0.05) tests. Results: MSH2 was overexpressed in OSCC (P=0.020) and was positive in 100% of patients with OL with dysplasia or OSCC (P=0.019). Positivity for MLH1 was significantly associated with comorbidity (P=0.040), especially in patients who presented with 2 or more pathologies (P=0.028). XRCC1 positivity was also associated with comorbidity (P=0.039). No significant associations were found for the MRE11A expression. Although the simultaneous positivity for the 4 markers was observed in presence of comorbidities (P=0.006). Conclusions: This study supports the effect of the overexpression of MSH2 protein in samples of OL with dysplasia and OSCC, most notably in patients who present with comorbidities and negativity for OL without dysplasia.
Keywords: cancer and precancer; DNA repair; immunopathology; mucosal diseases; oral squamous cell carcinoma